Architecting 3D prism shaped carbon dots/germanium/germanium oxide nanohybrid for photocatalytic degradation of pendimethalin and dinotefuran pesticides. (June 2022) - Dhenadhayalan, Namasivayam; Chauhan, Anuj; Lin, King-Chuen; AlFantazi, Akram
Abstract: A highly efficient photocatalyst 'carbon dots-reinforced germanium/germanium oxide' (CGGO) nanohybrid material was developed for an investigation of photocatalytic activity towards toxic insecticide [dinotefuran (DTF)] and herbicide [pendimethalin (PDM)]. The facile hydrothermal method was applied to synthesize CGGO with the presence of carbon dots (C-dots) as a reductant and shape tuner. A 3D-shaped nanoprism morphology of CGGO was acquired in which Ge/GeO2 was encapsulated by a carbon layer, whereas the nanosheets-like layer structure of reduced GeO2 (rGeO2 ) was observed in the absence of C-dots, revealing the shape tuning proficiency of C-dots. CGGO was exhibited superior photocatalytic activity under visible light illumination (>440 nm) as such ∼100% degradation of PDM and DTF was achieved in 22 and 14 min with a high rate constant of 0.1448 and 0.2503 min −1, respectively. The degradation mechanism was predominantly governed by the hydroxyl radical reaction of CGGO with pesticides, which was confirmed based on the catalytic reactions with reactive species scavengers. In addition, the photogenerated electrons were trapped by the carbon layer, which in turn suppresses the recombination of photogenerated electron and hole pairs leading to enhanced photocatalytic activity. The synergistic effects of Ge/GeO2 and C-dots make the CGGO nanohybrid a superior photocatalyst. Furthermore, reusable and practical applicability in real sample analyses were performed to validate the sustainability of nanohybrid. Graphical abstract: Image 1 Highlights: Biowaste (papaya seeds) material was used to prepare the carbon dots (C-dots). C-dots reinforced germanium/germanium oxide (CGGO) featured a 3D-shaped nanoprism. CGGO showed superior photocatalytic activity towards dinotefuran and pendimethalin.